2018
DOI: 10.1101/349001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A specific sequence in the genome of respiratory syncytial virus regulates the generation of copy-back defective viral genomes

Abstract: Defective viral genomes of the copy-back type (cbDVGs) are the primary initiators of the antiviral immune response during infection with respiratory syncytial virus (RSV) both in vitro and in vivo. However, the mechanism governing cbDVG generation remains unknown, thereby limiting our ability to manipulate cbDVG content in order to modulate the host response to infection. Here we report a specific genomic signal that mediates the generation of RSV cbDVGs. Using a customized bioinformatics tool, we identified r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 57 publications
2
26
1
Order By: Relevance
“…However, different from deletion and point mutation DVGs, copy-back DVGs are frequently found in discrete dominant populations in an infected cell or tissue, and the same copy-back DVG seems to arise in independent infections with the same parental virus 54,55 or during infections with different virus strains 56 . The demonstration of hotspots for the generation of copyback DVGs from respiratory syncytial virus (RSV) and the identification of specific nucleotides that determine where copy-back DVGs rejoin further demonstrate that the generation of copy-back DVGs is not completely random, but instead that specific sequences encoded in the viral genome direct or facilitate their formation 50 in some infections, DVG generation is not a completely stochastic process and, instead, virus-encoded sequences favour the production and/or amplification of predominant DVGs. It remains to be determined whether conservation is a property of certain DVG types and which specific sequences and/or RNA structures lead to DVG generation in these conditions.…”
Section: Mechanisms Of Dvg Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, different from deletion and point mutation DVGs, copy-back DVGs are frequently found in discrete dominant populations in an infected cell or tissue, and the same copy-back DVG seems to arise in independent infections with the same parental virus 54,55 or during infections with different virus strains 56 . The demonstration of hotspots for the generation of copyback DVGs from respiratory syncytial virus (RSV) and the identification of specific nucleotides that determine where copy-back DVGs rejoin further demonstrate that the generation of copy-back DVGs is not completely random, but instead that specific sequences encoded in the viral genome direct or facilitate their formation 50 in some infections, DVG generation is not a completely stochastic process and, instead, virus-encoded sequences favour the production and/or amplification of predominant DVGs. It remains to be determined whether conservation is a property of certain DVG types and which specific sequences and/or RNA structures lead to DVG generation in these conditions.…”
Section: Mechanisms Of Dvg Generationmentioning
confidence: 99%
“…While recent NGS data reveal that hundreds of DVGs can arise within a single viral infection, the fact that a smaller subset of dominant DVGs are repeatedly detected in different samples 50 indicates that complex dynamics are at play within the viral population. These complexities include competition (and possibly compensation or cooperation) between different DVGs and positive selection of the best competitors that implicates their relative fitness in relation to the wild-type parental virus and other DVGs.…”
Section: Impact On Viral Evolution and Dynamicsmentioning
confidence: 99%
“…Sequence-and factordependent pausing is well represented in the DNA-dependent RNA polymerase literature 45 . In case of the respiratory syncytial virus (RSV), sequences in the genome rich in G:C nucleotides were recently discovered that promote copy-back RNA synthesis 46 . In this system, these sequences alter polymerase elongation capacity 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In case of the respiratory syncytial virus (RSV), sequences in the genome rich in G:C nucleotides were recently discovered that promote copy-back RNA synthesis 46 . In this system, these sequences alter polymerase elongation capacity 46 . It is intriguing to speculate that these sequences promote backtracking.…”
Section: Discussionmentioning
confidence: 99%
“…However, the process of DVGs generation may not be as stochastic as initially proposed; previous studies have shown that specific sequences in the genome of vesicular stomatitis virus (VSV) favour the generation of defective RNAs (22). Additionally, a recent study has shown that the generation of DVGs in respiratory syncytial virus (RSV) infections may favour specific regions of the on September 2, 2020 by guest http://jvi.asm.org/ Downloaded from genome suggesting the existence of hotspots that act as rejoin points for the viral polymerase during the formation of copyback DVGs (23).…”
Section: Downloaded Frommentioning
confidence: 99%